Signifikansi Fitur Postingan Ulang di TikTok terhadap Ekspresi Diri pada Generasi Z - Dian Fitri Nuur’ Ainii; Hudi Santoso; Leonard Dharmawan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The increasing use of the repost feature on TikTok among Generation Z has prompted a study on how the feature plays a role in shaping self-expression in the digital space. This study uses a quantitative method with a survey of 92 students of SMA Negeri 6 Tangerang Regency to identify the effect of the intensity of repost feature use on the level of self-expression. Data were analyzed using reliability tests, validity, simple linear regression, t-test, and f-test. The results of the analysis show that the repost feature has a significant influence, indicated by the correlation coefficient and R regression value of 0.625 with an R Square of 0.391, meaning 39.1% of the variation in self-expression is explained by the use of the repost feature. The t-test produces a value of 7.602 (p = 0.000), further confirming this influence. The higher the intensity of repost feature use, the greater the level of self-expression shown by users, so this feature plays an important role as a means of self-representation and a means of building social connectedness for Generation Z on the TikTok platform.